Pedagogical Strategies and Content Knowledge of the Teacher of English for Maths in the Context of Content-Based Instruction - Fitrianingsih, Ayu; Udin, Syahrul (Language Circle: Journal of Language and Literature, 2017)
Teacher is a key person in teaching and learning process. The teacher must have good strategies to teach, they also have to know the goals to reach success and how they set the students realizing those goals. Besides, content knowledge is crucial owned by a teacher to create meaningful learning for students especially in Content-Based Instruction teaching and learning context. It becomes an issue once new idea to maximize the learning process and results. This study was intended to find the pedagogical strategies applied by the teacher in the teaching learning process and to know teacher‘s content knowledge, how teacher need to understand the subject matter taught. This study was carried out in English for Maths subject of Mathematics education study program IKIP PGRI Bojonegoro which involved the teacher and the students as the respondent. This study is under qualitative case study. In collecting the data, questionnaire, observation and interview were conducted to get detail information of the issues. The result reveals: 1) the teacher combines some methods such as cooperative learning, problem-based learning and task-based learning to get the students enthusiasm; 2) based on teacher‘s educational background, although the teacher graduated from Bachelor Degree of English Education but she was able to combine English teaching through mathematics content very well. It can be concluded that Teacher‘s pedagogical strategy and content knowledge is very important in the application of content-based instruction teaching and learning.